The Turkish Origins of Modern Egyptian Culture - Ezzat, Dina Aly (Selected Topics in Humanities and Social Sciences Vol. 9, 2022)
It is often assumed by scholars and visitors to Egypt that all or most componentss of Egyptian culture originated from the Pharaonic period. This assumption is, however, not accurate as over the centuries Egypt experienced occupation by outside powers that left their mark on the country. The aim of this chapter was to trace the Turkish origins of modern Egyptian culture. Data were obtained through analysis of historical documents, interviews of historians, experts and other officials at the Ministry of Antiquity, visits to various sites, including famous buildings and other landmarks. It was concluded that in almost every major area of culture, including government organization, education, the courts, medicine, law, and infrastructure Turkey heavily influenced Egypt. Indeed, many words used today in Egyptian Arabic are of Turkish origin. Conclusions derived offer a fuller accounting of how many aspects of this civilization had Turkish origins.